Visible light responsive nitrogen doped anatase TiO2 sheets with dominant {001} facets derived from TiN - Liu, G.; Hua, G.; Wang, X.; Cheng, L.; Pan, Jian; Gao, Q.; Cheng, H. (American Chemical Society, 2009)
(Graph Presented) We demonstrated a facile route for one-pot synthesis of visible light responsive nitrogen doped anatase TiO2 sheets with dominant {001} facets from TiN. The synthesized anatase TiO2 sheets show a strong and stable capability of generating photocatalysis active species of ·OH radicals and hydrogen evolution from splitting water under visible light irradiation. © 2009 American Chemical Society.